2021
DOI: 10.18203/2349-3291.ijcp20212036
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease in obese and overweight children

Abstract: Background: Childhood obesity is rising alarmingly and approaching an epidemic proportion in many countries. It increases the risk of developing non-communicable disease in adulthood. Non-alcoholic fatty liver disease (NAFLD) is a key co-morbidity associated with obesity and emerged as the leading cause of chronic liver disease in children. This study aimed to see the prevalence of the NAFLD with overweight and obesity among children.Methods:  It was a cross sectional study conducted among children aged 5.5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…18 NAFLD is a common complication associated with obesity in children, exhibiting a prevalence that spans from 1.7% to 85%. 7,18,19 In our study, NAFLD was identified in 63.4% of obese children of the same age group, through ultrasound testing. A comparable prevalence of 62% in obese children was also reported in the study by Gupta et al This study used Indian Academy of Paediatrics guidelines to define obesity while we followed WHO`s guidelines 20 .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…18 NAFLD is a common complication associated with obesity in children, exhibiting a prevalence that spans from 1.7% to 85%. 7,18,19 In our study, NAFLD was identified in 63.4% of obese children of the same age group, through ultrasound testing. A comparable prevalence of 62% in obese children was also reported in the study by Gupta et al This study used Indian Academy of Paediatrics guidelines to define obesity while we followed WHO`s guidelines 20 .…”
Section: Discussionmentioning
confidence: 59%
“…This finding aligns consistently with observations from various previous studies. [19][20][21][22][23][24] In our study, we noted that ALT levels ≥ 45 IU/L were present in 81.1% of patients diagnosed with NAFLD, in contrast to a lower occurrence of 18.9% in patients without NAFLD. Correspondingly, Akhtar et al, reported a significant elevation in ALT levels among children with NAFLD (58.3%) compared to those without NAFLD (16.7%).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations